The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2007
DOI: 10.1080/15563650601072159
|View full text |Cite
|
Sign up to set email alerts
|

Physostigmine for gamma-hydroxybutyrate coma: Inefficacy, adverse events, and review

Abstract: Physostigmine has been proposed as an antidote for gamma hydroxybutyrate (GHB) intoxication, based on associated awakenings in 1) patients anesthetized with GHB and 2) five of six patients administered physostigmine for GHB intoxication. However, there are neither well-supported mechanisms for physostigmine reversal of GHB effects, supportive animal studies, nor randomized, placebo-controlled trials demonstrating safety, efficacy, or improved outcomes. We sought to determine the outcomes of patients with GHB-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 36 publications
0
12
0
3
Order By: Relevance
“…17 Rohm et al found that physostigmine does not accelerate emergence after desflurane anesthesia, 18 and Zvosec et al reported that physostigmine is not effective for treating gamma-hydroxybutyrate intoxication. 39 …”
Section: Discussionmentioning
confidence: 99%
“…17 Rohm et al found that physostigmine does not accelerate emergence after desflurane anesthesia, 18 and Zvosec et al reported that physostigmine is not effective for treating gamma-hydroxybutyrate intoxication. 39 …”
Section: Discussionmentioning
confidence: 99%
“…The use of physostigmine is controversial, but most reports have found that it provides no clinical benefit 17–19. In addition, it reduces the convulsive threshold and may cause heart block 18. After recovery from coma, amnesia with respect to the preceding events is common 20…”
Section: Discussionmentioning
confidence: 99%
“…Management is supportive, with intubation only required for prolonged coma, airway security or other complications 43–45 . Antidotes such as physostigmine are not beneficial 46 …”
Section: Discussionmentioning
confidence: 99%